Konsep Al-Muwatanah dalam Perspektif Hadist Tarbawi - Arda Mei Lica; Dwi Meutia Hasni (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
Love for the homeland is one of the important character values that should be instilled in the younger generation to strengthen unity, nationalism, and national identity. In the era of globalization, various challenges such as the decline of national spirit and the erosion of character values have become significant concerns in the field of education. This study aims to analyze the concept of love for the homeland from the perspective of hadith tarbawi, identify the educational values contained within it, and explain the role of Islamic education in fostering nationalism among students. This research employs a library research method with a qualitative descriptive approach through the examination of the Qur’an, hadith, books, journals, and other relevant scholarly sources. The findings reveal that the value of love for the homeland is consistent with Islamic teachings, which emphasize unity, social responsibility, respect for diversity, and commitment to the nation and the state. Hadith tarbawi contains character education values that can serve as a foundation for developing students’ sense of nationalism. Furthermore, Islamic education and teachers play strategic roles as educators, role models, and mentors in internalizing the values of love for the homeland through both learning processes and daily practices. The implications of this study indicate that strengthening the value of love for the homeland based on hadith tarbawi can serve as an alternative approach to developing a generation with noble character, a strong national spirit, and the ability to maintain national unity and integrity within a diverse society.